Designing robust force control of hydraulic actuators despite system and environmental uncertainties. - Niksefat, N. (IEEE Control systems magazine)
The article presents the design of a robust force controller for a hydraulic actuator interacting with an uncertain environment via quantitative feedback theory (QFT). After the derivation of a realistic nonlinear differential equation model, a linearized plant transfer function is developed. The effects of nonlinearities are accounted for by describing the linearized model parameters as structured uncertainty. The impact of environmental variability as well as variations in hydraulic component parameters are also included as uncertainty in the model. The QFT design procedure is carried out to design a robust controller that satisfies performance specifications for tracking and disturbance rejection. The designed controller enjoys the simplicity of fixed-gain controllers, is easy to implement, and at the same time is robust to the variation of hydraulic functions as well as environmental stiffness. The controller is implemented on an industrial hydraulic actuator equipped with a low-cost proportional valve. The experimental results show that robust stability against system uncertainties and under varying conditions is achieved and the performance goals are satisfied